Preparation process of polymer coated guide wire and guide wire
Through sandblasting and plasma surface treatment, ideal surface roughness and tiny concave and convex structure are formed, which solves the problem of unsatisfactory bonding between the guide wire and the cladding layer, and improves the safety and durability of the guide wire.
Patent Information
- Application Number
- CN202411892994.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-21
AI Technical Summary
The bonding force of the existing guide wire in the core wire and the cladding layer is not ideal, which affects the safety and durability of the guide wire.
Sand blasting is used to form a rough sand surface, and a high-energy particle etching effect is introduced into the plasma surface treatment to form a smaller concave and convex structure, enhancing the binding force between the core wire and the polymer.
The bonding force between the core wire and the cladding layer is improved, the safety and durability of the guide wire are enhanced, while maintaining the shape memory characteristics of the nickel-titanium alloy.
Smart Images

Figure CN119656456A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of medical device production, and in particular to a preparation process of a polymer-coated guide wire and a guide wire. Background Art
[0002] As an important medical device, guidewire plays a key role in interventional therapy, angioplasty and other fields. It can effectively reduce the damage to patient tissues during surgery, improve the success rate of surgery and the recovery speed of patients. The application scope of guidewire is constantly expanding, not only limited to cardiovascular diseases, but also widely used in neurosurgery, urology, oncology and other medical fields. This makes the comprehensive performance requirements of guidewire higher, not only to have excellent mechanical properties and biocompatibility, but also to ensure stability and reliability for long-term use.
[0003] In order to meet the application requirements in the above-mentioned medical fields, the guide wire needs to have good flexibility and biocompatibility. Therefore, the guide wire generally comprises a core wire and a coating layer. The coating layer covers the surface of the core wire. The coating layer is generally made of a flexible polymer to improve the flexibility of the guide wire. The surface of the coating layer can also be coated with a functional coating to improve the biocompatibility of the guide wire.
[0004] However, there is currently a problem of unsatisfactory bonding between the core wire and the coating layer, which affects the safety and durability of the guidewire. Summary of the invention
[0005] In order to enhance the bonding strength between the core wire and the coating layer, the present application provides a preparation process of a polymer coated guide wire and a guide wire.
[0006] In a first aspect, the present application provides a preparation process of a polymer-coated guide wire using the following technical solution: A preparation process of a polymer-coated guide wire comprises the following steps: Clean the core wire surface; Performing sandblasting on the surface of the core wire to form a sand surface; Performing plasma surface treatment on the sand surface of the core wire to complete the pretreatment of the core wire; The polymer is melted to form a polymer melt, and the polymer melt is coated on the surface of the pretreated core wire, and cooled to form a polymer coating layer to obtain a guide wire.
[0007] By adopting the above technical solution, the sandblasting process forms a rough sand surface on the surface of the core wire, thereby increasing the surface friction and thus improving the bonding force between the core wire surface and the polymer.
[0008] The core wire is usually made of nickel-titanium alloy. The characteristics of nickel-titanium alloy make it difficult to achieve an ideal surface roughness without destroying its shape memory properties when the core wire is sandblasted. Too low surface roughness will lead to insufficient adhesion of the coating layer, while too high surface roughness will introduce microcracks and stress concentration points, affecting the overall performance of the guide wire.
[0009] After the sand surface is formed on the surface of the core wire, plasma surface treatment is performed. The high-energy particles generated by the plasma surface treatment impact the surface of the core wire, resulting in a microscopic etching effect, which can form a smaller concave-convex structure on the sand surface, achieve a more ideal surface roughness, and improve the surface hydrophilicity. The polymer can better penetrate into the tiny concave-convex structure of the core wire to form a stronger physical locking effect and maintain the shape memory properties of the nickel-titanium alloy. In addition, after the plasma surface treatment, active functional groups are introduced on the surface of the core wire to strengthen the crosslinking with the polymer, thereby enhancing the interface bonding performance of the two and improving the safety and durability of the core wire.
[0010] Optionally, the output power of the plasma surface treatment is 1500-1700 W, the treatment time is 20-40 s, the gas flow rate is 500-650 sccm, and the gas used for the plasma surface treatment is a mixed gas composed of argon and oxygen, wherein the oxygen flow rate accounts for 5-7%.
[0011] By adopting the above technical solution, on the basis of the sand surface that has been formed, the appropriate plasma treatment parameters are controlled, that is, higher output power and lower gas flow, so as to form a tiny concave-convex structure on the sand surface, which promotes the combination of polymer and core wire. If the plasma treatment parameters are not properly controlled, it may be difficult to form the ideal surface roughness, or the original sand surface may be "smoothed", reducing the hydrophilic angle and affecting the adhesion to the polymer.
[0012] Using oxygen as the active gas, the ions generated during ionization can bombard the surface and refine the uneven structure on the rough sand surface. Compared with using hydrogen as the active gas, oxygen ions have a better bombardment effect on the surface of nickel-titanium alloy. They can chemically react with the molecular chains after the bonds on the sand surface are broken to form active groups, thereby enhancing the ability of the core wire surface to combine with the polymer.
[0013] Optionally, the sandblasting treatment adopts liquid sandblasting, the mass ratio of shot blasting to water is 1:(5.6-9), the sandblasting time is 2-3.5s, the sandblasting pressure is 0.25-0.35MPa, and the sandblasting distance is 90-100mm.
[0014] By adopting the above technical solution, since the core wire is thin, liquid sandblasting is used to reduce the impact on the overall structure of the core wire, and the processing parameters of the liquid sandblasting are controlled to appropriately roughen the surface of the core wire, so as to obtain a more ideal roughness after subsequent plasma treatment.
[0015] Optionally, the size of the shot peening is 500-600 meshes.
[0016] By adopting the above technical solution, the shot peening with the above size can form a uniform sand surface on the surface of the core wire, achieving a delicate surface effect.
[0017] Optionally, the shot peening material is white corundum or garnet.
[0018] By adopting the above technical solution, the hardness of white corundum and garnet is high and the sandblasting effect is good.
[0019] Optionally, the polymer includes one or more of polyurethane, polytetrafluoroethylene and polylactic acid.
[0020] By adopting the above technical solution, the above polymer is coated on the surface of the guide wire, which can reduce the friction of the guide wire in human tissue, improve lubricity, and reduce the damage caused by the movement of the guide wire.
[0021] Optionally, the core wire is made of nickel-titanium alloy.
[0022] By adopting the above technical solution, nickel-titanium alloy has a shape memory effect, and its elasticity and toughness can meet the application treatment scenarios of the guide wire.
[0023] Optionally, the core wire surface is cleaned by ultrasonic cleaning.
[0024] By adopting the above technical solution, ultrasonic cleaning can clean the oil or dust on the surface of the core wire to improve the bonding force between the core wire surface and the polymer.
[0025] Optionally, the surface of the guide wire may also be coated with a hydrophilic coating, such as a coating containing polyvinyl pyrrolidone.
[0026] In the second aspect, the present application provides a guidewire adopting the following technical solution: A guide wire comprises a core wire and a polymer coating layer coated on the surface of the core wire.
[0027] In summary, this application has the following beneficial effects: 1. In the present application, sandblasting is used to form a rough sand surface on the surface of the core wire to increase surface friction. After the sand surface is formed on the surface of the core wire, plasma surface treatment is performed. The high-energy particles generated by the plasma surface treatment impact the surface of the core wire, resulting in a microscopic etching effect, which can form a smaller concave-convex structure on the sand surface to achieve a more ideal surface roughness. The polymer can better penetrate into the tiny concave-convex structure of the core wire to form a stronger physical locking effect and maintain the shape memory properties of the nickel-titanium alloy. In addition, after the plasma surface treatment, active functional groups are introduced on the surface of the core wire to strengthen the crosslinking with the polymer, thereby enhancing the interface bonding performance of the two and improving the safety and durability of the core wire.
[0028] 2. Control the appropriate plasma treatment parameters, that is, higher output power and lower gas flow, so as to form tiny concave-convex structures on the sand surface and promote the combination of polymer and core wire. Using oxygen as the active gas, the ions generated during ionization can bombard the surface and refine the uneven structure on the rough sand surface. The oxygen ions have a better bombardment effect on the surface of nickel-titanium alloy, and can react chemically with the molecular chains after the bond is broken on the sand surface to form active groups, which strengthens the ability of the core wire surface to combine with the polymer. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a cross-sectional structural diagram of the guidewire of Example 1 of the present application.
[0030] Description of reference numerals: 1. Core wire; 2. Polymer coating. DETAILED DESCRIPTION
[0031] The following is combined with Figure 1 This application is described in further detail.
[0032] The present application discloses a guide wire, such as Figure 1 As shown, a guide wire includes a core wire 1 and a polymer coating 2, the core wire 1 is made of nickel-titanium alloy, the straight section outer diameter of the core wire 1 is 0.4 mm, the polymer coating 2 is coated on the surface of the core wire 1, the material of the polymer coating 2 is any one of polyurethane, polytetrafluoroethylene and polylactic acid, and the overall outer diameter of the guide wire is 0.79 mm.
[0033] Example 1 The present application also discloses a preparation process of a polymer-coated guide wire, comprising the following steps: S1. Clean the core wire surface.
[0034] The surface of the core wire is cleaned by ultrasonic cleaning. Specifically, the core wire is placed in an ultrasonic cleaning machine filled with a cleaning agent, which may be water or a surfactant cleaning agent, specifically water in this embodiment, and the core wire is soaked and cleaned at an ultrasonic frequency of 30kHz for 10 minutes, and dried after cleaning to complete the cleaning.
[0035] S2. Sandblasting is performed on the surface of the core wire to form a sand surface.
[0036] The core wire is sandblasted by liquid sandblasting. Specifically, the core wire is placed in a wet sandblasting machine, the mass ratio of shot blasting to water in the abrasive liquid is 1:5.6, the sandblasting time is 2s, the sandblasting pressure is 0.35MPa, and the sandblasting distance is 90mm. The shot blasting uses a size of 500-600 mesh, and the material of the shot blasting is white corundum.
[0037] S3. Plasma surface treatment is performed on the sand surface of the core wire to complete the pretreatment of the core wire.
[0038] The core wire is placed in a plasma surface treatment machine, and gas is introduced after vacuuming. The output power of the plasma surface treatment is 1500W, the treatment time is 40s, the gas flow rate is 500sccm, and the gas used for the plasma surface treatment is a mixed gas composed of argon and oxygen, in which the oxygen flow rate accounts for 7%.
[0039] S4. Melting the polymer to form a polymer melt, coating the polymer melt on the surface of the pretreated core wire, cooling, forming a polymer coating layer, and obtaining a guide wire.
[0040] The polymer melt is coated on the surface of the core wire by extrusion coating. Specifically, the polymer is polyurethane, more specifically MDI / PPG type thermoplastic polyurethane, which can be obtained commercially. The core wire is inserted into the extrusion die, and the polymer is melted at 170°C by the extruder to form a polymer melt. The polymer melt flows into the extrusion die, so that the polymer melt coats the core wire in the extrusion die. After the core wire passes through the extrusion die, it enters the cooling medium for cooling to form a polymer coating layer, which is dried to obtain a guide wire.
[0041] Example 2 The present application also discloses a preparation process of a polymer-coated guide wire, comprising the following steps: S1. Clean the core wire surface.
[0042] The surface of the core wire is cleaned by ultrasonic cleaning. Specifically, the core wire is placed in an ultrasonic cleaning machine filled with a cleaning agent, which may be water or a surfactant cleaning agent, specifically water in this embodiment, and the core wire is soaked and cleaned at an ultrasonic frequency of 30kHz for 10 minutes, and dried after cleaning to complete the cleaning.
[0043] S2. Sandblasting is performed on the surface of the core wire to form a sand surface.
[0044] The core wire is sandblasted by liquid sandblasting. Specifically, the core wire is placed in a wet sandblasting machine, the mass ratio of shot blasting to water in the abrasive liquid is 1:9, the sandblasting time is 3.5s, the sandblasting pressure is 0.25MPa, and the sandblasting distance is 100mm. The shot blasting uses a size of 500-600 mesh, and the material of the shot blasting is white corundum.
[0045] S3. Plasma surface treatment is performed on the sand surface of the core wire to complete the pretreatment of the core wire.
[0046] The core wire is placed in a plasma surface treatment machine, and gas is introduced after vacuuming. The output power of the plasma surface treatment is 1700W, the treatment time is 20s, the gas flow rate is 650sccm, and the gas used for the plasma surface treatment is a mixed gas composed of argon and oxygen, in which the oxygen flow rate accounts for 5%.
[0047] S4. Melting the polymer to form a polymer melt, coating the polymer melt on the surface of the pretreated core wire, cooling, forming a polymer coating layer, and obtaining a guide wire.
[0048] The polymer melt is coated on the surface of the core wire by extrusion coating. Specifically, the polymer is polyurethane, more specifically MDI / PPG type thermoplastic polyurethane, which can be obtained commercially. The core wire is inserted into the extrusion die, and the polymer is melted at 170°C by the extruder to form a polymer melt. The polymer melt flows into the extrusion die, so that the polymer melt coats the core wire in the extrusion die. After the core wire passes through the extrusion die, it enters the cooling medium for cooling to form a polymer coating layer, which is dried to obtain a guide wire.
[0049] Example 3 The difference between this embodiment and embodiment 1 lies in S3.
[0050] S3. Plasma surface treatment is performed on the sand surface of the core wire to complete the pretreatment of the core wire.
[0051] The core wire is placed in a plasma surface treatment machine, and gas is introduced after vacuuming. The output power of the plasma surface treatment is 1000W, the treatment time is 40s, the gas flow rate is 1000sccm, and the gas used for the plasma surface treatment is a mixed gas composed of argon and oxygen, in which the oxygen flow rate accounts for 7%.
[0052] Example 4 The difference between this embodiment and embodiment 1 lies in S2.
[0053] S2. Sandblasting is performed on the surface of the core wire to form a sand surface.
[0054] The core wire is sandblasted by liquid sandblasting. Specifically, the core wire is placed in a wet sandblasting machine, the mass ratio of shot blasting to water in the abrasive liquid is 1:3.3, the sandblasting time is 2s, the sandblasting pressure is 0.6MPa, and the sandblasting distance is 90mm. The shot blasting uses a size of 500-600 mesh, and the material of the shot blasting is white corundum.
[0055] Comparative Example 1 A preparation process of a polymer-coated guide wire comprises the following steps: S1. Clean the core wire surface.
[0056] The surface of the core wire is cleaned by ultrasonic cleaning. Specifically, the core wire is placed in an ultrasonic cleaning machine filled with a cleaning agent, which may be water or a surfactant cleaning agent, specifically water in this embodiment, and the core wire is soaked and cleaned at an ultrasonic frequency of 30kHz for 10 minutes, and dried after cleaning to complete the cleaning.
[0057] S2. Melting the polymer to form a polymer melt, coating the polymer melt on the surface of the cleaned core wire, cooling, forming a polymer coating layer, and obtaining a guide wire.
[0058] The polymer melt is coated on the surface of the core wire by extrusion coating. Specifically, the polymer is polyurethane, more specifically MDI / PPG type thermoplastic polyurethane, which can be obtained commercially. The core wire is inserted into the extrusion die, and the polymer is melted at 170°C by the extruder to form a polymer melt. The polymer melt flows into the extrusion die, so that the polymer melt coats the core wire in the extrusion die. After the core wire passes through the extrusion die, it enters the cooling medium for cooling to form a polymer coating layer, which is dried to obtain a guide wire.
[0059] Comparative Example 2 A preparation process of a polymer-coated guide wire comprises the following steps: S1. Clean the core wire surface.
[0060] The surface of the core wire is cleaned by ultrasonic cleaning. Specifically, the core wire is placed in an ultrasonic cleaning machine filled with a cleaning agent, which may be water or a surfactant cleaning agent, specifically water in this embodiment, and the core wire is soaked and cleaned at an ultrasonic frequency of 30kHz for 10 minutes, and dried after cleaning to complete the cleaning.
[0061] S2. Sandblasting is performed on the surface of the core wire to form a sand surface.
[0062] The core wire is sandblasted by liquid sandblasting. Specifically, the core wire is placed in a wet sandblasting machine, the mass ratio of shot blasting to water in the abrasive liquid is 1:5.6, the sandblasting time is 2s, the sandblasting pressure is 0.35MPa, and the sandblasting distance is 90mm. The shot blasting uses a size of 500-600 mesh, and the material of the shot blasting is white corundum.
[0063] S3. Melting the polymer to form a polymer melt, coating the polymer melt on the surface of the core wire forming the sand surface, cooling, forming a polymer coating layer, and obtaining a guide wire.
[0064] The polymer melt is coated on the surface of the core wire by extrusion coating. Specifically, the polymer is polyurethane, more specifically MDI / PPG type thermoplastic polyurethane, which can be obtained commercially. The core wire is inserted into the extrusion die, and the polymer is melted at 170°C by the extruder to form a polymer melt. The polymer melt flows into the extrusion die, so that the polymer melt coats the core wire in the extrusion die. After the core wire passes through the extrusion die, it enters the cooling medium for cooling to form a polymer coating layer, which is dried to obtain a guide wire.
[0065] Comparative Example 3 A preparation process of a polymer-coated guide wire comprises the following steps: S1. Clean the core wire surface.
[0066] The surface of the core wire is cleaned by ultrasonic cleaning. Specifically, the core wire is placed in an ultrasonic cleaning machine filled with a cleaning agent, which may be water or a surfactant cleaning agent, specifically water in this embodiment, and the core wire is soaked and cleaned at an ultrasonic frequency of 30kHz for 10 minutes, and dried after cleaning to complete the cleaning.
[0067] S2. Performing plasma surface treatment on the core wire surface.
[0068] The cleaned core wire is placed in a plasma surface treatment machine, and gas is introduced after vacuuming. The output power of the plasma surface treatment is 1500W, the treatment time is 40s, the gas flow rate is 500sccm, and the gas used for the plasma surface treatment is a mixed gas composed of argon and oxygen, in which the oxygen flow rate accounts for 7%.
[0069] S3. Melting the polymer to form a polymer melt, coating the polymer melt on the surface of the core wire, cooling, forming a polymer coating layer, and obtaining a guide wire.
[0070] The polymer melt is coated on the surface of the core wire by extrusion coating. Specifically, the polymer is polyurethane, more specifically MDI / PPG type thermoplastic polyurethane, which can be obtained commercially. The core wire is inserted into the extrusion die, and the polymer is melted at 170°C by the extruder to form a polymer melt. The polymer melt flows into the extrusion die, so that the polymer melt coats the core wire in the extrusion die. After the core wire passes through the extrusion die, it enters the cooling medium for cooling to form a polymer coating layer, which is dried to obtain a guide wire.
[0071] Comparative Example 4 S1. Clean the core wire surface.
[0072] The surface of the core wire is cleaned by ultrasonic cleaning. Specifically, the core wire is placed in an ultrasonic cleaning machine filled with a cleaning agent, which may be water or a surfactant cleaning agent, specifically water in this embodiment, and the core wire is soaked and cleaned at an ultrasonic frequency of 30kHz for 10 minutes, and dried after cleaning to complete the cleaning.
[0073] S2. Performing plasma surface treatment on the core wire surface.
[0074] The core wire is placed in a plasma surface treatment machine, and gas is introduced after vacuuming. The output power of the plasma surface treatment is 1500W, the treatment time is 40s, the gas flow rate is 500sccm, and the gas used for the plasma surface treatment is a mixed gas composed of argon and oxygen, in which the oxygen flow rate accounts for 7%.
[0075] S3. Sandblasting is performed on the surface of the core wire to form a sand surface.
[0076] The core wire is sandblasted by liquid sandblasting. Specifically, the core wire is placed in a wet sandblasting machine, the mass ratio of shot blasting to water in the abrasive liquid is 1:5.6, the sandblasting time is 2s, the sandblasting pressure is 0.35MPa, and the sandblasting distance is 90mm. The shot blasting uses a size of 500-600 mesh, and the material of the shot blasting is white corundum.
[0077] S4. Melting the polymer to form a polymer melt, coating the polymer melt on the surface of the core wire, cooling, forming a polymer coating layer, and obtaining a guide wire.
[0078] The polymer melt is coated on the surface of the core wire by extrusion coating. Specifically, the polymer is polyurethane, more specifically MDI / PPG type thermoplastic polyurethane, which can be obtained commercially. The core wire is inserted into the extrusion die, and the polymer is melted at 170°C by the extruder to form a polymer melt. The polymer melt flows into the extrusion die, so that the polymer melt coats the core wire in the extrusion die. After the core wire passes through the extrusion die, it enters the cooling medium for cooling to form a polymer coating layer, which is dried to obtain a guide wire.
[0079] Effect test The following tests were performed on the guidewires of the same size prepared in Examples 1-4 and Comparative Examples 1-4.
[0080] Peeling force test: Use a universal tensile testing machine to pull up both ends of the guide wire respectively, and observe the change in force value until the force value tends to stabilize from an upward trend. At this time, the polymer coating peels off from the surface of the core wire, and the maximum force value when it is stable is recorded as the peeling force.
[0081] Hydrophilic angle test: Use a contact angle tester to evaluate the surface wettability of the core wire before it is coated with a polymer. Fix the test material on the test bench, adjust the height and position of the test liquid (water) dropper, ensure that the liquid can accurately drip on the material surface and measure the contact angle between the droplet and the material surface. When the contact angle is less than 90°, the material surface is considered to be hydrophilic, that is, the liquid spreads easily on the material surface; when the contact angle is greater than 90°, the material surface is considered to be hydrophobic, that is, the droplets formed by the liquid on the material surface present a more rounded shape.
[0082] The above test results are shown in Table 1.
[0083] Table 1 Peeling force (N) Hydrophilic angle (°) Example 1 55.2 28.3 Example 2 54.3 30.3 Example 3 47.0 37.5 Example 4 49.5 35.6 Comparative Example 1 32.7 75.7 Comparative Example 2 38.5 66.4 Comparative Example 3 36.0 70.6 Comparative Example 4 41.9 55.3 Compared with the comparative example 1 in which the core wire surface is not treated and directly coated with polymer, the peeling force is only 32N. After the guide wire is coated with polymer after sandblasting and plasma treatment, the peeling force is significantly enhanced to 55N, and the guide wire maintains good structural strength, which proves that the bonding strength between the core wire and the coating layer is enhanced, thereby improving the safety and durability of the guide wire.
[0084] It can be seen from the test results of Example 1 and Comparative Examples 2-4 that sandblasting and plasma treatment interact with each other on the surface of the core wire. In order to reduce the impact of sandblasting on the structure of the guide wire itself, the degree of sandblasting needs to be controlled within a lower range. If only sandblasting is performed, the hydrophilic angle is large and the bonding force between the core wire and the coating is insufficient. If only plasma treatment is performed, there is a lack of sufficient contact area to promote the adhesion of the coating, and the hydrophilic angle cannot be significantly improved. Therefore, sandblasting first and then plasma treatment can obtain a good interface bonding effect on the core wire surface.
[0085] It can be seen from the test results of Example 1 and Examples 3-4 that while sandblasting and plasma treatment improve hydrophilicity, controlling a higher output power and a lower gas flow rate during plasma treatment, as well as controlling the concentration of shot in the abrasive liquid during sandblasting, helps to form tiny concave-convex structures on the sand surface, further promote the contact between the polymer melt and the core wire surface, and improve the bonding adhesion between the core wire and the coating layer.
[0086] This specific implementation manner is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the specific implementation manner as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A process for preparing a polymer-coated guide wire, characterized in that: The following steps are involved: Clean the core wire surface; Performing sandblasting on the surface of the core wire to form a sand surface; Performing plasma surface treatment on the sand surface of the core wire to complete the pretreatment of the core wire; The polymer is melted to form a polymer melt, and the polymer melt is coated on the surface of the pretreated core wire, and cooled to form a polymer coating layer to obtain a guide wire.
2. The process for preparing a polymer-coated guide wire according to claim 1, characterized in that: The output power of plasma surface treatment is 1500~1700W, the processing time is 20~40s, the gas flow rate is 500~650sccm, and the gas used for plasma surface treatment is a mixed gas composed of argon and oxygen, among which the oxygen flow rate accounts for 5~7%.
3. The process for preparing a polymer-coated guide wire according to claim 1, characterized in that: The sandblasting treatment adopts liquid sandblasting, the mass ratio of shot blasting to water is 1:(5.6~9), the sandblasting time is 2~3.5s, the sandblasting pressure is 0.25~0.35MPa, and the sandblasting distance is 90~100mm.
4. The process for preparing a polymer-coated guide wire according to claim 1, characterized in that: The size of the shot peening is 500-600 mesh.
5. The process for preparing a polymer-coated guide wire according to claim 1, characterized in that: The material of the shot peening is white corundum or garnet.
6. The process for preparing a polymer-coated guide wire according to claim 1, characterized in that: The polymer includes one or more of polyurethane, polytetrafluoroethylene and polylactic acid.
7. The process for preparing a polymer-coated guide wire according to claim 1, characterized in that: The polymer melt is coated on the surface of the core wire in an extrusion coating manner.
8. The process for preparing a polymer-coated guide wire according to claim 1, characterized in that: The material of the core wire is nickel-titanium alloy.
9. The process for preparing a polymer-coated guide wire according to claim 1, characterized in that: The surface of the core wire is cleaned by ultrasonic cleaning.
10. A guide wire, prepared based on the preparation process of the polymer-coated guide wire according to any one of claims 1 to 9, comprising a core wire and a polymer coating layer coated on the surface of the core wire.
Citation Information
Patent Citations
Manufacturing process of loach guide wire
CN114209959A
Forming process of high-wear-resistance yarn guide for textile industry
CN117444542A
PEEK / TPU double-layer medical catheter based on melt adhesion after plasma modification and preparation method of PEEK / TPU double-layer medical catheter
CN118681067A
Medical guide wire
CN206138556U